A new species of eleotridid, Eleotris tecta, from Pacific slope streams of tropical America (Pisces: Eleotrididae) - Bussing, William A (1996)
The "pygmy sleeper" of the farnily Eleotrididae, Eleotris tecta, is described as new on the basis of tbe values of several counts, differences in neuromast paneros on the head and differences in fin coloration. The eight known specimens were taken in small freshwater streams close to tbe sea in soutbern Costa Rica, and in Colombia (rnainland and Isla Gorgona). The new species is more similar to E. tubularis, an endemic in streams on Isla del Coco, than witb its congener E. picta, which is known from California to Pero and is reported bere for the first time from Isla del Coco